ASSESSMENT OF PHYSICO -CHEMICAL PARAMETERS OF MAYO INNE RIVER, ADAMAWA STATE, NIGERIA. - BATURE, A.A.; ABUBAKAR, A.K.; CHINTEM, W.D.G; BINGARI, M.S; JONATHAN, J. (Nigerian Journal of Fisheries, 2017)
This study assessed the physico-chemical parameters of River Mayo Inne, Fufore Local Government, Adamawa state, Northeast Nigeria. Four locations were chosen spatially along the water course to reflect a consideration of all possible human activities that are capable of changing the water quality of the river. Water samples were collected monthly for six consecutive months (July-Dec. 2014) at the four sampling stations. pH, water temperature (℃), conductivity (µs/cm) were analyzed in-situ while dissolved oxygen (mg/L), nitrate (mg/L), phosphate (mg/L), alkalinity (mg/L) were determined ex-situ using standard methods. Physico-chemical parameters Result showed that dissolved oxygen, temperature, transparency, hydrogen ion, freeCO2, Phosphorus, Ammonia, Alkalinity concentration fall within the permissible limit of WHO for drinking water and fish production. The physico-chemical parameters in river Mayo Inne generally fall within acceptable limits.